Konstruksi Klausa Makian pada Partisipan Usia Tua dalam Bahasa Melayu Bengkulu - Eli Rustinar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to describe the construction of invective clause markers in old age participants. The research method is qualitative. Data and data sources are insults derived from Bengkulu Malay language informants. Data collection methods and techniques through listening and introspection. The method of listening uses the basic techniques of tapping techniques outlined in the advanced technique, which is a free trial of competent involvement (SBLC), record, and record. Stages of providing data through three activities, namely collecting, selecting, and structuring. Analytical methods and techniques use contextual analysis, peer review, and distribution or distribution. There is a construct of marking invective clauses on parental participants: namely: 1) based on the position of the elements of the clause shows that the invective tends to be within the invective core clause, 2) based on function analysis, invective tends to occupy the predicate function (P) which is positioned in front of the subject (S) i.e. position (PS), 3) the use of the second persona pronominal as a mark of curse clauses indicates the tendency of invective use in intimate / intimate participants, 4) the use of clits - it is that the curse clause functions to emphasize imperative sentences and reinforcement designations in cursing sentences so that the utterances become coarser and the level of emotional expression of anger becomes higher. Conclusions, construction of invective clauses on parental participants includes; elemental position, function analysis, pronominal, and clit usage Keywords: Curse, Old Age, Clause, Bengkulu Malay Language